Flapping‐Wing Dynamics as a Natural Detector of Wind Direction. (9th November 2020) - Tanaka, Kazutoshi; Yang, Shih-Hsin; Tokudome, Yuji; Minami, Yuna; Lu, Yuyao; Arie, Takayuki; Akita, Seiji; Takei, Kuniharu; Nakajima, Kohei
Abstract : Flapping‐wing unmanned aerial vehicles have potential advantages, such as consuming lower energy by leveraging the force of wind. Since the flapping movements of the soft wings contain information about the wind, measuring the movement of each part of the wings allows these vehicles to distinguish the direction of the wind. To confirm this prediction, herein, the detection of wind flow from the flapping‐wing motion of a bird robot using an integrated flexible strain sensor on its wing and a physical reservoir computing analysis is presented. In the presence of different wind directions, the movement of the flapping‐wings is measured using flexible strain sensors, and the current wind direction is detected by capitalizing on the intrinsic wing dynamics. As a result, it is found that the detection accuracy using our embedded flexible strain sensors is significantly high, showing a similar level of accuracy with a high‐speed camera recorded from the fixed position in the environment. The results indicate that flapping‐wing unmanned aerial vehicles can recognize wind direction by exploiting the natural dynamics of their wings. Abstract : Herein, the detection of wind flow from the flapping‐wing motion of a bird robot using an integrated flexible strain sensor on a wing and a physical reservoir computing approach is presented. The results suggest that flapping‐wing unmanned aerial vehicles can detect wind direction by exploiting the natural dynamics of their wings.